Pengenalan Bahasa Inggris pada Siswa Kelas 3 di SDN 1 Samuda Kecil melalui Metode Video Interaktif - Josilia Puspito Rahayu; Nuur Anisa; Munirah Munirah (Jurnal Kemitraan Masyarakat, 2024)
English has become an important subject at the elementary school level, unlike when it was introduced at the middle school level. Today, English is included in the curriculum of elementary schools, as well as in kindergartens and early childhood education. English is introduced through enjoyable informal methods, such as playing and singing, to align with students' development. This aims to provide a strong foundation in foreign language acquisition. However, teaching English in remote areas like Samuda Kecil still faces challenges, such as a lack of resources and facilities. Digital technology, such as interactive videos from YouTube, is one innovation that has addressed these obstacles. The community service group at Institut Agama Islam Negeri Palangka Raya, who teaches at SDN 1 Samuda Kecil, uses the interactive video "Days of the Week" as a teaching medium. This video helps students listen to correct pronunciations and increases their motivation to learn. As a result, students find it easier to remember vocabulary and show significant improvement in understanding the material. Interactive media like this has proven effective in enhancing the quality of English learning in remote areas.